Corticosteroid Inhalation in the Treatment of Childhood Asthma - Munasir, Zakiudin; Knol, Klaas (Indonesian Pediatric Society, 1990)
Inhaled corticosteroids are a dramatic advance in the therapy of chronic asthma. Corticosteroid inhalation therapy in children offers the same advantages over oral medication as in adults. Inhaled corticosteroid has a better effects compared with other prophylactic antiasthma therapy such as theophylline, sodium cromoglycate and ketotifen. However, it is obvious that inhaled corticosteroids are not completely free of side effects, both topical and systemic such as suppresiion of hypothalamus-pituitary adrenal-axis (HPA), growth retardation, osteoporosis, cataract formation, blood count and immunoglobulin changes, oropharyngeal candidiasis and dysphonia. Recently, many clinicians have been using this effective and save treatment more freely and for longterm administration.